Digital Financial Strategy: New Direction or the Usual Old? - Kerekes, László (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
This paper explores the intricate relationship between technology and law, specifically delving into the legal regulation of technology. The author addresses the challenges posed by cybercrime in the context of IoT devices and blockchain technology. The research focuses on digital financial strategy, particularly its connection to blockchain technology. Employing a descriptive and comparative methodology, the study then introduces the technology underlying cryptocurrencies and subsequently examines the issues about the Digital Financial Package of the European Union. The findings highlight that the digital finance strategy represents one of the most significant and comprehensive legislative packages in recent years.